Impact of Role Conflict on Intention to Leave Job With the Moderating Role of Job Embeddedness in Banking Sector Employees - Awan, Fazal Hussain; Dunnan, Liu; Jamil, Khalid; Gul, Rana Faizan; Anwar, Aliya; Idrees, Muhammad; Guangyu, Qin (Frontiers in Psychology, 2021)
This study investigates why some employees intend to leave their jobs when facing the conflict between family responsibilities and job routines. The present study also reveals the moderating role of on-the-job embeddedness between role conflict and intention to leave the job. Drawing on conservation of resources theory, the paper investigates the buffering effect of the three on-the-job embeddedness components (fit, links and sacrifice). Data were collected from banking officers because most of the employees have to face role conflict between family and job responsibilities as banking job is considered the most stressful job. Collected data were analyzed by applying structural equation modelling. Results indicate that the role conflict significantly influences on intention to leave the job. Furthermore, the study shows that on-the-job embeddedness moderates the relationship between role conflict and intention to leave. The results suggest that organizations can reduce turnover intention during work and life conflict times by developing employee on-the-job embeddedness. This study provides some insights to managers why many employees leave their jobs and how to overcome this problem. Management should also offer extra and available resources in periods of greater tension to minimize early thinking regarding quitting.